The Misconceptions Analysis of Regulatory System Materials Using Four-Tier Diagnostic Test Instruments - Rahmatika, Atik Yusni; Utami, Nur Rahayu (FMIPA UNNES, 2021)
The results of the 2018 PISA survey showed a decrease in the quality ranking of Indonesian education, so it is necessary to evaluate the difficulties of students in learning. One of the difficulties encountered is that students are unable to understand concepts precisely or misconceptions as agreed by scientists. Student misconceptions need to be identified because it will have a bad impact on students, one of which is low learning outcomes. This study aims to analyze the profile of grade XI students' misconceptions on regulatory system material with a four-tier diagnostic test instrument. The samples of this study were students of Class XI MIPA 1, XI MIPA 2, XI MIPA 3, and XI MIPA 4 SMA Negeri 2 Semarang with a total of 143 students. This type of research is descriptive research with non-experimental quantitative methods. The four-tier diagnostic test instrument in this study consisted of 20 items. Each question has four levels of answers; At the first level, there are four choices of answers and one choice of open answers, the second level is the level of confidence, at the third level there are four choices of reasons and one choice of open reasons, and the fourth level is the level of confidence. The results of the misconception analysis of SMA Negeri 2 Semarang students showed that 25% of the misconceptions were in the low category. Of the 4 types of combination answers to misconceptions, type 1 was 52%; type 2 at 3,5%; type 3 at 5,5%; and type 4 as much as 39% of the total 685 answers that fall into the misconception category. In general, the causes of student misconceptions are student assumption, lack of literacy, and lack of time to study.